CRIMINAL JUSTICE SYSTEM IN ERADICATION OF CORRUPTION IN INDONESIA - Bambang Dwi Baskoro; Hartiwiningsih Hartiwiningsih; Hari Purwadi (Diponegoro Law Review, 2018)
Criminal Justice System  in eradication corruption is spesialisation in around General Trial, not yet the same as Usually Criminal Justice System. It’s not  integrated  like normal  criminal  justice  system, because  each other  institution  work  in  criminal justice system  itself  so  appearance  the fragmentaris  and  egosectoral.The regulating in Law  is criminal justice systemsin  eradication  corruption  emplacedCorruption Eradication Commission ( KPK)  as  coordinator, supervision, trigger mechanism institution besides  as  investigators  and  prosecutor  corruption.